Forensic Characteristics of Crimes in the Field of Trafficking in Narcotic Drugs, Psychotropic Substances, Their Analogues or Precursors - D. V. Golovin (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The most topical problems of the elements of forensic characteristics of crimes in the field of trafficking in narcotic drugs, psychotropic substances, their analogues or precursors have been revealed. It has been established that this category of crimes existed and exists in all countries and types of society. The author has determined the criminogenic characteristics inherent to the offender and how his / her behavior is manifested during the commission of crimes in this area.